Safety and efficacy of an essential oil from Origanum vulgare ssp. hirtum (Link) Ietsw. for all animal species - Bampidis, Vasileios (EFSA J, 2019)
Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on an essential oil extracted from Origanum vulgare ssp. hirtum (Link) Ietsw. when used as a sensory feed additive for all animal species. Analysis of the oil identified 13 components accounting for > 99% of the oil, with carvacrol being the prevalent (78%). The FEEDAP Panel concludes that the proposed use level of 150 mg/kg complete feed is safe for ornamental fish. For the other species, the calculated maximum safe concentration of the essential oil in complete feed was 22 mg/kg for chickens for fattening, 33 mg/kg for laying hens, 30 mg/kg for turkeys for fattening, 40 mg/kg for piglets, 48 mg/kg for pigs for fattening, 63 mg/kg for sows, 57 mg/kg for dairy cows, 100 mg/kg for veal calves, 88 mg/kg for cattle for fattening, sheep, goats and horses, 35 mg/kg for rabbits, 101 mg/kg for salmonids, 106 mg/kg for dogs, and 18 mg/kg for cats. No concerns for consumer safety were identified following the use of the additive up to the maximum safe concentration in feed. The additive is considered as irritant to skin and eyes and a potential skin and respiratory sensitiser. Use in animal husbandry of the essential oil extracted from O. vulgare ssp. hirtum is not expected to pose a risk for the environment. Since oregano and its preparations are recognised to flavour food and their function in feed would be essentially the same, no further demonstration of efficacy is considered necessary for the essential oil.